A data envelopment analysis approach for measuring the efficiency of Canadian acute care hospitals. (August 2014) - Fixler, Tamás; Paradi, Joseph C; Yang, Xiaopeng
Data envelopment analysis is a methodology particularly well-suited to measuring the efficiency of hospitals because it is able to accommodate multiple heterogeneous inputs and outputs in order to model the complex relationships that exist within them. This research uses data envelopment analysis to develop a model of Canadian hospital production efficiency in collaboration with the Canadian Institute for Health Information. The model is intended to illustrate the utility of data envelopment analysis as a hospital performance measurement tool for Canadian Institute for Health Information and to augment their current hospital performance indicators. The model measures the overall production efficiency of acute care hospitals using labour and capital inputs together with outputs measuring inpatient and outpatient activity. The model also includes non-discretionary variables adjusting for case-mix variations among the hospitals. The model is extensively validated and identifies a set of highly referenced, efficient hospitals ideal for the establishment of best practices.